Clinical supervision in the real world : a practical guide to ethics, legal issues, and personal development - Martin, Francis A.; Turner, Janet P. (New York, NY : Routledge, 2020)
"This practical guide provides support for mental health practitioners as they develop their approach to clinical supervision, drawing on the authors' extensive experience of counseling and psychotherapy to bring readers into the 'real world' of clinical supervision. Chapters introduce the essential responsibilities and tasks of a clinical supervisor and place emphasis on the development of a Competence Oriented Model of Clinical Supervision, upon which a philosophical foundation for supervision can be built"--
OCLC-licensed vendor bibliographic record.
Keywords: Psychotherapists -- Supervision of; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health